Sunan Kalijaga dan strategi dakwah melalui Tembang Lir-Ilir - Yusuf Bakti Nugraha; Lutfiah Ayundasari (Universitas Negeri Malang, 2021)
The problem that this article tries to address is about how the role of Wali Songo, especially in this discussion, is Sunan Kalijaga who uses art as a medium of preaching. In this case he used the song Lir-ilir which has a philosophical meaning in the aspect of religion. Of course this song is not just an artistic entertainment, but the message contained in this song is so deep that it is very suitable to be able to help the propagation of the spread of Islamic teachings. Even so, along with the development of the times, it is feared that this kind of culture and arts could be eroded because of the negative influences that follow from the swift currents of globalization, so that it is so difficult to maintain. Masalah yang coba dituangkan dalam artikel ini yakni tentang bagaimana peranan Wali Songo khususnya pada pembahasan ini adalah Sunan Kalijaga yang menggunakan seni untuk media dakwah. Dalam hal ini beliau menggunakan tembang Lir-ilir yang memiliki makna filosofi dalam aspek agama. Tentunya tembang ini bukan sekedar hiburan seni, melainkan memang pesan yang terkandung dalam tembang ini begitu dalam sehingga begitu cocok untuk bisa membantu dakwah penyebaran ajaran Islam. Meski begitu seiring dengan berkembangnya zaman, dikhawatirkan budaya dan kesenian seperti ini dapat tergerus karena pengaaruh negatif yang ikut dari arus globalisasi yang deras sehingga begitu sulit untuk dipertahankan.